Loneliness mediates the association between insecure attachment and mental health among university students. (February 2022) - Nottage, Matilda K.; Oei, Nicole Y.L.; Wolters, Nine; Klein, Anke; Van der Heijde, Claudia M.; Vonk, Peter; Wiers, Reinout W.; Koelen, Jurrijn
Abstract: Insecure attachment is a transdiagnostic personality factor which may confer risk for mental health issues. The mechanisms underlying this association may be partly explained by loneliness. Loneliness, which is common in young adulthood, also concerns social relationships and is similarly associated with negative mental health outcomes. This study investigates whether insecure attachment styles are associated with an increase in mental health issues, specifically depressive symptoms and problematic alcohol use, and whether this link is mediated by loneliness. Students at a Dutch university ( n = 265) aged 17 to 43 completed an online survey assessing attachment (ECR-SF), loneliness (DJGLS-11), social connectedness (LSNS-6), depression (PHQ-9) and alcohol use (AUDIT-C). Results showed that in individuals with mixed attachment styles (scoring high on both the anxious and avoidant dimensions), loneliness mediated the positive association between attachment style and depressive symptoms. Exploratory moderated mediation, with social connectedness as a moderator, showed that loneliness mediated the attachment-depression relationship in socially connected, anxiously attached young adults. Similar results were found for alcohol use although the direction differed, with lonelier students drinking less. These findings' implications are discussed considering future research and the potential of interventions targeting loneliness from an attachment perspective. Highlights: Insecure attachment styles are associated with increased depressive symptoms. Loneliness mediates this link in students with mixed attachment styles. Loneliness mediates this link in anxiously attached students who are socially well-connected. A similar pattern was found between attachment style and problem drinking. Attachment style should be considered in interventions targeting student loneliness.